Dental students' knowledge about protective guidelines for clinical practice during the COVID‐19 pandemic - Atefe Saffar Shahroudi; Sedighe-Sadat Hashemikamangar; Zainab Ali Ahmed Aljawad; Behnaz Behniafar (Elsevier, 2023)
Objective: The coronavirus disease 2019 (COVID-19) originated in China, in December 2019, spread worldwide promptly and turned into an outbreak which caused an international public health concern. The novel coronavirus which is also called SARS-CoV-2 transmits predominantly by respiratory droplets and the spread pattern of this infection throughout the community became a big challenge encountering the dental profession. Recently several guidelines have been developed for dental clinicians to protect both patients and practitioners, agents this infection. The aim of this study was to estimate the knowledge of dental students about the content of protective guidelines for clinical practice during the COVID‐19 pandemic. Methods: An online questionnaire was developed by a team of specialists which were the faculty member of Tehran University of Medical sciences according to the content of the protective guidelines of ADA for dental practice during the COVID‐19 pandemic. The questionnaire was validated and its reliability was confirmed by retesting 10 samples after 2 weeks with a cronbach alpha of 0.9. The online questionnaire was sent to 4 dental schools in the city of Tehran and was fill out by 170 dental students. Results: The mean knowledge score for all 170 participants was 16.23 out of 32 (50.72%) with the maximum score of 24 (75.0%) and the minimum score of 1 (3.1%). There was a significant relationship between the gender of participants and their knowledge score (p = 0.032) in the way that male students had significantly higher score than females. Students with more advanced educational level achieved higher knowledge scores. (p = 0.038) However, there were no significant correlation between other variables and the students' knowledge score. (p > 0.05) Conclusion: Dental students had acceptable knowledge about the general protocols against corona virus in terms of hand hygiene, wearing face masks, surface sanitization and diagnostic symptoms of a patient susceptible to be infected by corona virus. However, mostly they were not aware of the details of the guideline's items which makes it crucial to add related content in the dental students' educational curriculum.